Sistem Informasi Ekspor Ikan Bandeng Di CV Fish Asia - Elis Diana Manzil; Wisnu Yudo Untoro; Nonot Wisnu Karyanto (Melek IT : Information Technology Journal, 2016)
“Export is selling cross country which would involve the two parties to do cross-selling transactions. Export done by CV Fish Asia namely export fish whitefish. The processing of transactions that occur on the current Asian Fish CV is still much done manually so that manual process may sometimes result in slow performance in handling the export transaction. The resolution of an issue that occurs on a CV that is with Asian Fish make an Export information system includes inventory, sales transactions and purchase transaction.” “Based on the research that has been carried out then the author can provide information those transactions contained in the CV Fish Asia.”